Entwicklung und Validierung eines Fragebogens zur standardisierten Selbsteinschätzung emotionaler Kompetenzen (SEK-27) - Berking, Matthias; Znoj, Hansjörg (Zeitschrift für Psychiatrie, Psychologie und Psychotherapie, 2008)
Background: Deficits and resources in general emotion-regulation skills have been shown to be important for the development, maintenance and treatment of mental disorders. Objective: In order to be able to economically assess a wide range of helpful ways of dealing with negative emotions, the Fragebogen zur Selbsteinschätzung Emotionaler Kompetenzen (SEK-27) has been developed and validated. Methods: Using data from two normal control samples (N = 952) and three clinical samples (N = 238), a variety of indicators of test quality were computed. Results: Findings confirm the reliability, validity and change sensitivity of the questionnaire. Conclusions: The SEK-27 is an economical self-report measure with appropriate psychometric properties that can be used to assess a broad range of adaptive ways of dealing with negative emotions. © 2008 by Verlag Hans Huber, Hogrefe AG.
Created from Fastlane, Scopus look-up
Keywords: Assessment; Emotion regulation; Emotion regulation skills; Emotional intelligence; Psychotherapy